Potential use of citrus pectin as flocculants in water turbidity reduction - Mendoza, Raisa A.; Tan, Irene L. (2012)
The study utilized fruit waste materials as sources of pectic and examined their potential in treating turbid water. Pectin was extracted from the peels of Citru microcarpa (calamansi) and Citrus decumama (suha). The efficiency of the citrus pectins as flocculants were tested and compared to alum by measuring their flocculating activities. Also, the effect of varying flocculant dosages on reducing the turbidity of the synthetic turbid water (kaolin solution) was examined. The results show that as the concentration of the flocculant increases, the turbidity of the kaolin solution decreases. There is a significant difference (p<0.05) between the three flocculants and the negative control. However, there is no significant difference in the percent flocculation activity between alum, Citrus microcarpa, and Citrus decumama. Maximum turbidity reduction by the Circus microcarpa (calamansi) flocculant was 87.85 plus/minus 8.51%; while Citrus decumama (suha) flocculant had 92.03 plus/minus 2.73% turbidity removal; and aluminum sulfate had 90.70 plus/minus 9.5% turbidity removal. Results imply that Citrus microcarpa (calamansi) and Citrus decumama (suha) have the potential as natural flocculants in water treatments.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Citrus pectin -- Flocculants